C-H functionalization of pyridines - Maity, Susmita; Bera, Asish; Bhattacharjya, Ayantika; Maity, Pradip (Organic & Biomolecular Chemistry, 2023)
Pyridine and its reduced form (piperidine) are the most common nitrogen heterocycles in FDA-approved drugs. Additionally, their presence in alkaloids, ligands for transition metals, catalysts, and organic materials with various properties makes them among the most important structural cores. Despite its importance, direct and selective functionalization of pyridine remains scarce due to its electron-poor nature and nitrogen coordination power. Instead, functionalized pyridine rings were primarily constructed from suitably substituted acyclic precursors. The focus on sustainable chemistry with minimum waste generation encourages chemists to develop direct C-H functionalization. This review summarizes different approaches to tackle the reactivity and regio- and stereoselectivity aspects for direct pyridine C-H functionalization.